Assessment on diversity and bioactive compounds present in endophytic fungi isolated from Rhizophora mucronata in Matang Mangrove Forest Reserve, Perak, Malaysia - Tuan Hamzah, Tuan Noraida (2018)
Rhizophora mucronata is an important ecosystem entity of the Malaysian mangrove forest. Because the tree grows in an extreme environment, any organism that is isolated from this tree is of huge interest due to its potential in having novel bioactive compounds. This study aimed to assess endophytic fungal diversity isolated from mangrove plant, R. mucronata, to evaluate the bioactivities exhibited by selected fungal endophytes, and to isolate and identify compounds associated with the selected endophytic fungi extracts. In the present work, a total of 78 fungal isolates were isolated, identified and characterized from the leaf tissues of R. mucronata. All strains were identified using primer internal transcribed spacer 1 (ITS1) and internal transcribed spacer 4 (ITS4). The DNA sequences of the strains recorded high similarities to their respective species in the GenBank. Phylogenetic trees were constructed and analyzed using Maximum Likelihood (ML) criteria together with 78 mangrove endophytic fungal sequences and 117 additional sequences of fungal species incorporated from the GenBank. Most of the dominating fungal endophytes were from the genus Pestalotiopsis, followed by Alternaria and Cladosporium. Six isolates representing the genera Alternaria, Fusarium, Nigrospora, Pestalotiopsis, Phoma, and Xylaria, were screened for their antagonism activities. The antagonism tests were evaluated through dual culture and non-volatile compound assay. Dual culture test assay revealed their inhibition percentages against the phytopathogenic fungus Fusarium solani between 49-69%, and 1-25% when using non-volatile test assay. The fungal isolates were further screened for their antibacterial activities against four pathogenic bacteria, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. Of the six isolates, only Fusarium lateritium and Xylaria sp. showed antibacterial activities against tested bacteria, with the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) ranging from 0.5 to 2 mg/mL. The 1,1-diphenyl-2-picrylhydrazyl(DPPH) radical scavenging assay recorded antioxidant activity in Xylaria sp. with 3-fold higher when compared to F. lateritium. The chemical constituents of F. lateritium and Xylaria sp. were determined via Gas Chromatography (GC) with Mass Spectrometry (MS) and Flame Ionization Detector (FID). These two fungal species were chosen based on their positive activities in several assays conducted in the previous section before, including, antagonism, antibacterial and antioxidant assay. Overall, 69 compounds were identified from ethyl acetate and hexane extracts of F. lateritium and Xylaria sp..Compounds such as phenylethyl alcohol, phenylacetic acid, cetene, and 2,4-Ditert-butylphenol, were commonly found in all the extracts of both fungal species. Variations of constituents were found in all extracts for both fungal isolates. Hexane extracts of F. lateritium and Xylaria sp. both recorded a greater variation in chemicals identified. While there were almost similar compounds identified from ethyl acetate extracts of both fungal isolate. Evaluation on the biological activities exhibited by F. lateritium and Xylaria sp. before, with the presence of these compounds, proved that these two fungal isolates have great potential as antimicrobial agents. Screening the endophytic fungal community associated with Rhizophora mucronata, and bioactivities exhibited by the selected isolates has proved that mangroves endophytic fungi could be a potential source in finding the bio-control agent and another important source for vital bioactive compounds.